Advances in control and data transmission over the power line using the ultra-wideband technology approach - Jamaluddin J.E.; See O.H. (2023)
The concerns of having a high speed data transmission over power line carriers can be resolved with many techniques including modulation and encoding schemes and synchronization techniques. The ultra wideband technology implemented in radio communication provides a better performance in a wired environment with fewer problems and as efficient as combined wireless and wired technologies for networking. The ultra-wideband (UWB) technology has advantage in terms of low signal to noise ratio, low spectral density, less complexity and easy modulation schemes. The fact that power line communication has been working with OFDM makes the UWB favorable. This paper looks into the performance of generalized ultra-wideband pulses by means of emulating the Gaussian pulse variance using the M-ary Phase Shift Keying (PSK) modulation schemes and the results in channel capacity and bit error rate (BER) performance. 2010 IEEE.